Conceptualising risk in cruise holidays: A critical review. (24th August 2021) - Holland, Jennifer; Weeden, Clare; Palmer, Catherine; Lester, Jo‐Anne
Abstract: The knowledge base for cruise holidays is conceptually underdeveloped and narrowly focused on health and safety and environmental concerns. This critical review of risk research in relation to ocean cruising identifies knowledge gaps revealing the significance of factors such as financial, performance, time‐loss, opportunity, functional, social and psychological risk. This review calls for a wider conceptualisation of risk that moves beyond an emphasis on physical risk. A deeper understanding of risk in ocean cruising contributes to cruise research and to the wider discourse in tourism and risk studies, and provides significant empirical and conceptual insights for future research.